Novel variant in MYH9 in a child with proteinuria and thrombocytopenia: a case report and literature review - Xie, Dan-Feng; Zhu, Lin; Wang, Xiao-Meng; Li, Yun; Zhou, Ping (Frontiers in Pediatrics, 2025)
There is a lack of awareness of the diagnosis and treatment of MYH9-related disorder (MYH9-RD), which is an autosomal dominant disease with heterogeneous clinical manifestations. We summarized the clinical phenotype and reported a novel variant in MYH9 in a child with focal segmental glomerulosclerosis (FSGS) and reviewed the relevant literature to better understand MYH9-RD. Unlike previous cases, this patient exhibited IgA deposition in the mesangial region, suggesting need for further investigation into prognostic and therapeutic significance of this finding. To reduce the risk of MYH9-RD misdiagnosis, we recommend assessing mean platelet diameter and granulocyte inclusions in patients with unexplained proteinuria and refractory thrombocytopenia.